2014
DOI: 10.3389/fpsyg.2014.00906
|View full text |Cite
|
Sign up to set email alerts
|

Does awareness affect the restorative function and perception of street trees?

Abstract: Urban streetscapes are outdoor areas in which the general public can appreciate green landscapes and engage in outdoor activities along the street. This study tested the extent to which the degree of awareness of urban street trees impacts attention restoration and perceived restorativeness. We manipulated the degree of awareness of street trees. Participants were placed into four groups and shown different images: (a) streetscapes with absolutely no trees; (b) streetscapes with flashes of trees in which parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 56 publications
6
53
0
Order By: Relevance
“…In the short term, application and enhancements of the technique used here might be informative in joining the gap between remote sensing studies [14,15], studies of individual subjects in the field [16] or lab [8]. Possible applications include looking at routes taken to work and school or the relationship between objects in the environment versus those consciously perceived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the short term, application and enhancements of the technique used here might be informative in joining the gap between remote sensing studies [14,15], studies of individual subjects in the field [16] or lab [8]. Possible applications include looking at routes taken to work and school or the relationship between objects in the environment versus those consciously perceived.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al [8] demonstrated that drawing attention to street trees in images increased restorativeness value of those images suggesting that cognition has a role to play. Even in studies where awareness isn’t the main subject participants have their attention drawn to the natural aspects of the scenes as part of the procedure [3].…”
Section: Introductionmentioning
confidence: 99%
“…To increase literacy and numeracy, children need to have access to nature, and at the very least, green and natural views of trees (Berman, Jonides, & Kaplan, ; Faber Taylor, Kuo, & Sullivan, ; Lin, Tsai, Sullivan, Chang, & Chang, ; Tennessen & Cimprich, ). As reviewed in Kuo, Browning, Sachdeva, Lee, and Westphal (), stress levels, concentration, and intrinsic motivation are likely strong factors in a child's success as a student.…”
Section: The Scientific Benefit Of Treesmentioning
confidence: 99%
“…To increase literacy and numeracy, children need to have access to nature, and at the very least, green and natural views of trees (Berman, Jonides, & Kaplan, 2008;Faber Taylor, Kuo, & Sullivan, 2002;Lin, Tsai, Sullivan, Chang, & Chang, 2014;Tennessen & Cimprich, 1995).…”
Section: Cognitive Development and Educationmentioning
confidence: 99%
“…Research shows that about 90% of the information received by people in the environment comes from vision. The most commonly seen green landscape amongst residents is 3-D greening, as represented by street greening and neighbourhood trees [10]. The visual evaluation of 3-D greening enables an intuitive understanding of the greening level in residential areas [11].…”
Section: Introductionmentioning
confidence: 99%